Efeitos da restrição de sono e exercício no metabolismo e imunidade - Fernandes, Leandro [UNIFESP] (2016)
The daily activities such as job, leisure, care of children, studies and others, have leaded the world population to reduce the hours of sleep. The effects of sleep loss are widely studied and known, promoting cognitive and metabolic changes. On the other hand, the physical exercise has been stimulated for general population with the aim of improving health and quality of life. However, the metabolic consequences of physical exercise in chronically sleep-restricted individuals are unknown. Thus, the objective of present study was evaluated if the physical exercise could minimize the deleterious effects resulting of sleep restriction in metabolic and immunological parameters. Therefore, we recruited 11 male, young and healthy volunteers who underwent sleep restriction for 3 nights followed by an acute bout of exercise of moderate intensity in treadmill (exhaust test). To assess the consequences of the physical exercise and sleep restriction (RS), previously the volunteers performed the same exhaustion test in habitual sleep condition (SH) (± 8 hours). Total sleep of volunteers was reduced by approximately 50% and there were no differences in parameters related to body composition. Although they showed no significant differences in fasting glucose, an increase above the normal glucose values after the RS was observed and, the acute physical exercise was effective in lowering blood glucose levels similar to SH condition. Interestingly, we observed a decrease of triglycerides and VLDL-cholesterol after RS, which remained lower after completion of the physical exercise. No hormones or cytokines change between SH and RS were observed. Accordingly, these data indicate that even in sleep loss condition, the physical exercise must be stimulated for the specific population studied, since it was observed an improvement of glucose metabolism without impairing other parameters.